Health Impacts and Recovery From Prolonged Freshwater Exposure in a Common Bottlenose Dolphin (Tursiops truncatus) - Deming, Alissa C.; Wingers, Noel L.; Moore, Debra P.; Rotstein, David; Wells, Randall S.; Ewing, Ruth; Hodanbosi, Matthew R.; Carmichael, Ruth H. (Frontiers in Veterinary Science, 2020)
Common bottlenose dolphins (Tursiops truncatus) exposed to freshwater or low salinity (<10 practical salinity units; PSU) for prolonged periods of time have been documented to develop skin lesions, corneal edema and electrolyte abnormalities, and in some instances they have died. Here we review a case of an out-of-habitat subadult, female common bottlenose dolphin that remained in a freshwater lake in Seminole, Alabama for at least 32 days. Due to concerns for the dolphin’s health a rescue was initiated. At the time of rescue bloodwork results indicated minor electrolyte abnormalities (hyponatremia, hypochloremia, hypoosmolality). Renal function was not affected (normal creatinine and urea nitrogen) and all other bloodwork parameters (hemogram; serum biochemistry analytes) were within normal limits. The dolphin was deemed healthy enough for immediate relocation and release. A satellite-linked tag was attached to the dorsal fin to track the dolphin following its relocation to a nearby brackish water bay (Perdido Bay, AL), a known habitat for bottlenose dolphins. Twelve weeks following release, the dolphin was found dead as a result of a fisheries interaction (peracute underwater entrapment). A full necropsy was conducted and here was complete resolution of the skin pallor and skin lesions and no evidence of chronic renal or central nervous system lesions. Postmortem analysis of vitreous humor (used as a proxy for serum analytes and to determine postmortem interval) was challenging to interpret and has not been validated in dolphins. This supports the need for future research in cetaceans to establish a species-specific approach. Elevated barium (Ba) concentrations in tooth dentin corresponded to increased seasonal freshwater discharge patterns, confirming repeated annual exposure to low salinity conditions prior to death and indicating freshwater exposure may pose an ongoing threat to dolphins in the region. This case provides a unique opportunity to follow the progression of prolonged freshwater exposure and recovery in a bottlenose dolphin and highlights that dolphins in nearshore habitats face a combination of persistent natural and human associated threats.